2018
DOI: 10.22323/2.17030201
|View full text |Cite
|
Sign up to set email alerts
|

What do people know about climate change ― and how confident are they? On measurements and analyses of science related knowledge

Abstract: The measurement and analysis of people's knowledge on scientific topics, such as climate change, is challenging for researchers. One reason is that objectives are multi-dimensional and that probability is inherent. Moreover, uncertainties can exist on the individual's level among the public, but are rarely grasped by existing scales. Therefore, researchers must thoroughly consider what to measure and how. This paper theorizes five different dimensions of climate change knowledge. Three response scales includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 55 publications
(121 reference statements)
1
14
0
2
Order By: Relevance
“…gives respondents a 50% random chance to answer correctly to a format allowing respondents to indicate the level of certainty in their answers (Taddicken, Reif, & Hoppe, 2018). Answers for the 11 items were combined in an index: correct answers gave respondents one point for the "likely" and two points for the "definitely" version.…”
Section: Methodology Datamentioning
confidence: 99%
“…gives respondents a 50% random chance to answer correctly to a format allowing respondents to indicate the level of certainty in their answers (Taddicken, Reif, & Hoppe, 2018). Answers for the 11 items were combined in an index: correct answers gave respondents one point for the "likely" and two points for the "definitely" version.…”
Section: Methodology Datamentioning
confidence: 99%
“…This research built on previous scholarship by Taddicken, Reif and Hoppe [2018], which identified that knowledge is a nuanced construct for which determining appropriate measurements is challenging. Our findings show there can be advantages of using one scale over the other.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond comparisons between factual and subjective knowledge, some scholars have pointed attention toward subtler differences that may be impacting knowledge assessment [e.g. Taddicken, Reif and Hoppe, 2018]. Most public opinion scholarship that incorporates a measurement of factual knowledge asks participants' responses to a series of true/false indicators.…”
Section: Objectivementioning
confidence: 99%
See 2 more Smart Citations